AKTIVITAS PENYEMBUHAN LUKA BAKAR FRAKSI DARI EKSTRAK ETANOL 70% DAUN PEPAYA (Carica papaya L.) PADA TIKUS BURN WOUND HEALING ACTIVITY FRACTION OF 70% ETHANOL EXTRACT OF PAPAYA LEAVES (Carica papaya L.) ON THE RATS - Muthmaina, Ina (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2017)
Papaya leaves could be used as an alternative traditional medicine by Indonesian people, such as  burn wound healing. This research  was aimed to find out  the activity of  fraction polar, semi-polar and  non-polar papaya leaves (Carica papaya L.) and which  fraction  has better activity as healing of burn wound  on rats. About 25 male rats are divided into five groups: positive control (Bioplacenton®), negative control (Gel bases) and three variations of the fraction (polar, semi-polar and non-polar) which was  topically administered 2 times a day. A metal heat was pasted on the back skin of rats for 30 seconds to induce burn wound. Burn wound diameter was observed on days 3rd, 6th, 9th, 12th  and 15th  with 2 parameters, burn wound  diameter reduction and day when the wound was shutted faster. The results showed that papaya leaf polar fraction with 2.16% dose has an activity as a burn wound healing  which was  begin on day 6th, while the fraction of non-polar and semi-polar fraction of papaya leaf with  0.02% dose has an activity as a burn wound healing which was begin on day 9th and 12th. Keyword : Carica papaya L., Burn Wound